Motility and Ultrastructure of Spirochaeta thermophila - Wirth, Reinhard; Ugele, Matthias; Wanner, Gerhard (Frontiers in Microbiology, 2016)
We analyze here for the first time the swimming behavior of a thermophilic, strictly anaerobic Spirochete, namely Spirochaeta thermophila using high temperature light microscopy. Our data show that S. thermophila very rapidly can change its morphology during swimming, resulting in cells appearing nearly linear, in cells possessing three different spiral forms, and in cells being linear at one end and spiral at the other end. In addition cells can rapidly bend by up to 180°, with their ends coming into close contact. We combine electron with light microscopy to explain these various cell morphologies. Swimming speeds for cells with the various morphologies did not differ significantly: the average speed was 33 (+/- 8) µm/s, with minimal and maximal speeds of 19 µm/s and 59 µm/s, respectively. Addition of gelling agents like polyvinylpyrrolidone or methyl cellulose to the growth medium resulted in lower and not higher swimming speeds, arguing against the idea that the highly unusual cell body plan of S. thermophila enables cells to swim more efficiently in gel-like habitats.